(untitled) (Al-Qamar, 2022)
This research paper aims to scrutinize the image of Spain in the light of the travelogue of Dr. Husain Mounis, in which he portraits the biographical aspects of Spain. It is all about beautiful landscapes, historical buildings, grand mosques, beautiful cities, culture, customs, and traditions of the people in a very unique and fascinating manner. Travelogue is an important part of literature in any of the world languages. All the nations are fond of Traveling and Journey since ancient times. The journey has gained special importance in Islamic literature and many scholars have been known to be adventurous travelers in different periods of time. Dr. Hussain Mounis is also one of them. He looks at the situation anywhere from a different perspective, making his travel journey different from the other and portraits the beautiful Picture of Andulas. This paper consists of a preface, two chapters and a conclusion. In the introduction, an importance of travelogue has been given. In the 1st chapter gives brief introduction of Dr. Hussain Mounis and his contributions in the field of Arabic language. The 2nd chapter explains the portrait of Andulas.